Tokyo revengers. 17-18 - Wakui, Ken (Seven Seas Entertainment, 2024)
After hearing Inui's heartfelt plea, Takemichi agrees to become the eleventh-generation leader of the Black Dragons, but there's no time to reflect on his newfound responsibility. The final showdown between Tenjiku and Toman is looming closer, and every day that goes by, the odds get worse and worse for Toman. Tenjiku is like no other enemy they've fought before--eager to fight dirty, ready to go to any lengths to take all of Toman's toughest fighters off the field before the battle even begins. And the worst is yet to come, as Kisaki Tetta prepares a ruthless scheme that will strike at the very heart of Toman!